Exploring potential neuroprotective properties of aqueous Centella asiatica extract in chronic stress-induced rats - Abdul Wahab, Muhamad Zulhusni; Zainal Abidin, Muhammad Zaim; Zakaria, Fatin Nadzirah; Mohd Moklas, Mohamad Aris; Amom, Zulkhairi; Hashim, Nina Keterina; Dasiman, Razif (Universiti Putra Malaysia Press, 2019)
Centella asiatica is one of the traditional herbs consumed by many communities due to its wide range of applications such as treating Parkinsonism, promoting memory enhancement, and preventing oxidative stress. This study was conducted to investigate the neuroprotective potential of aqueous C. asiatica extract (CAE) against neurodegeneration induced by chronic stress. Administration of CAE at three different dosages (200 mg/kg/day, 400 mg/ kg/day and 800 mg/kg/day) was conducted for a period of 21 days along with exposure to chronic stress using restrainer and forced swimming regimes. The administration of CAE significantly improved the thickness of dentate gyrus and reduced the amount of neuronal cell death at dentate gyrus and CA3 (p<0.05). Additionally, administration of CAE significantly alleviated the expression c-fos protein (p<0.05). Thus, this study highlighted the neuroprotective effect of CAE against neurodegeneration from chronic stress exposure.